Optimalisasi kemampuan komunikasi matematis siswa SMP kelas VII melalui pendekatan realistic mathematics education (RME) - Hayani, Nandita Nurlaelatul; Zanthy, Luvy Sylviana; Anita, Ika Wahyu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
The aim of this research is to find out whether the application of the Realistic Mathematics Education (RME) approach can improve students' mathematical communication skills. When compared with conventional learning, the results are better. The research method and design used is an experimental method (True Experimental Design) with Pretest-Posttest Control Group Design. The research population was class VII students at SMPN 3 Cipeundeuy. The samples studied were students in class VII-A as the experimental class and VII-B as the control class, with a total of 32 students in each class. The data collection technique used in this research is pretest and posttest data. Then the data was processed using Microsoft Excel 2013 and IBM SPSS Statistics 26 software. The results of data processing showed that Ho was rejected and H1 was accepted. So it can be concluded that the achievement of students' mathematical communication skills who use the Realistic Mathematic Education (RME) approach is better than those who use conventional learning.